Handbook for the Preparation of Landfill Gas to Energy Projects in Latin America and the Caribbean - Conestoga-Rovers & Associates (World Bank, Washington, DC, 2014)
This Handbook has been developed for the World Bank to facilitate the development of landfill gas (LFG) management and landfill gas to energy (LFGTE) projects in Latin America and the Caribbean (LAC). It is expected that the Handbook will be used by those who, own, operate, engineer and regulate landfill sites in LAC as a roadmap for the assessment of candidate projects and to initiate development of LFG management projects. The Handbook is intended as a practical guideline that uses background information and a number of instructive tools to educate, guide and establish a basis for decision-making, technical feasibility assessment, economics assessment, and market evaluation of all aspects necessary for developing successful LFG management projects. The Handbook, it has been organized and presented in three distinct parts, with each part comprised of a number of sections. Section 1 provides an introduction to the overall format of the Handbook and a brief description of the Sections that comprise Part I, Part II and Part III. It also provides the prospective team with a summary of expected information needed to take the project to the Contract Execution Phase. Part 1 is comprised of sections that allow the reader to gain a technical understanding of the LFG resource and potential use of the fuel and is organized to provide a basic understanding of both the LFG resource and all of the elements. Part II looks at the energy and environmental policies, legislation, regulations and the current energy markets. It also provides an insight into the policies that help mitigate environmental and social problems resulting from existing solid waste management practices and to implement systems that minimize the potential future issues. Part III of the Handbook presents the possible approaches and information necessary for assessing LFG management projects at landfill sites and to provide specific guidance for the assessment and development for a specific project in LAC.